Blockade of 2-arachidonoylglycerol hydrolysis produces antidepressant-like effects and enhances adult hippocampal neurogenesis and synaptic plasticity - Zhang, Zhen (Hippocampus, 2014)
The endocannabinoid ligand 2-arachidonoylglycerol (2-AG) is inactivated primarily by monoacylglycerol lipase (MAGL). We have shown recently that chronic treatments with MAGL inhibitor JZL184 produce antidepressant- and anxiolytic-like effects in a chronic unpredictable stress (CUS) model of depression in mice. However, the underlying mechanisms remain poorly understood. Adult hippocampal neurogenesis has been implicated in animal models of anxiety and depression and behavioral effects of antidepressants. We tested whether CUS and chronic JZL184 treatments affected adult neurogenesis and synaptic plasticity in the dentate gyrus (DG) of mouse hippocampus. We report that CUS induced depressive-like behaviors and decreased the number of bromodeoxyuridine (BrdU)-labeled neural progenitor cells and doublecortin-positive immature neurons in the DG, while chronic JZL184 treatments prevented these behavioral and cellular deficits. We also investigated the effects of CUS and chronic JZL184 on a form long-term potentiation (LTP) in the DG known to be neurogenesis-dependent. CUS impaired LTP induction, whereas chronic JZL184 treatments restored LTP in CUS-exposed mice. These results suggest that enhanced adult neurogenesis and long-term synaptic plasticity in the DG of the hippocampus might contribute to antidepressant- and anxiolytic-like behavioral effects of JZL184.